Order flow in the South: Anatomy of the Brazilian FX market - Thomas Wu (University of California, Economics Department, 2007)
This paper analyses one of the main pillars of Brazil.s newly found economic resilience: a maturing FX market providing support to its managed .oating exchange rate regime. I develop a microstrucure model suitable to describe the Brazilian FX market, an emerging economy frequently subjected to sudden stops in capital .ows. The model introduces two major changes relative to previous microstructure models. First, dealers may decide to hold overnight positions in the FX market if they .nd it pro.table to do so. Second, customers. demand for foreign exchange is a function of macroeconomic fundamentals, including contemporaneous feedback from exchange rate movements. The main predictions of the model are supported by a unique data set, covering all transactions between dealers and customers from the o cial Brazilian FX market from July 1, 1999 to June 30, 2003 (a time period in which Brazil suered two severe external liquidity shocks).
Keywords: F31; F41; G15; 330; Microstructure; Exchange Rates; Dealers; Liquidity; Central Bank Intervention; Devisenmarkt; Wechselkurs; Mikrostrukturanalyse; Wechselkurspolitik; Brasilien